Characteristics of resident physicians accessing a specialised mental health service: a retrospective study - María Dolores Braquehais; Sergi Valero; Eugeni Bruguera; Gemma Nieva; Sebastián Vargas-Cáceres; Maria Fernanda Mantilla; Germán Ortega; Jose Antonio Ramos-Quiroga (BMJ Open)
Objectives Little is known about resident physicians being treated at physician health programmes around the world despite the fact that it is a highly demanding training period. This study aims to describe the profiles of resident physicians accessing a specialised mental health service in Spain over a 20-year period and to compare them to consultant-grade physicians.Design Retrospective observational study.Setting Medical records of the Galatea Care Programme for Sick Physicians.Participants 1846 physicians registered at the Barcelona Medical Council-Association and admitted to the programme from January 1998 to December 2018.Primary and secondary outcome measures Number of admissions, sociodemographic and clinical variables, including medical specialty, main diagnosis and need of hospitalisation.Results Residents accounted for 18.1% (n=335) of the sample and admissions increased over the years. Most residents (n=311; 94.5%) and consultant-grade physicians (n=1391; 92.8%) were self-referred. The most common specialty among residents was family medicine (n=107; 31.9%), followed by internal medicine (n=18; 5.4%), paediatrics (n=14; 4.2%), psychiatry (n=13; 3.9%) and anaesthesiology (n=13; 3.9%). Residents, regardless of year of training, mainly asked for help because of adjustment (n=131; 39.1%), affective (n=77; 23%), anxiety disorders (n=40; 18.8%) and addictions (n=19; 5.7%). There were no significant differences between groups in the main diagnosis and in the variables related to need of hospitalisation. The percentage of residents accessing the programme was higher than in the reference population registered at the Barcelona Medical Council-Association (18.1% vs 7.6%; z=7.2, p<0.001) as was the percentage of family medicine residents (31.9% vs 19.6%; z=5.7, p<0.001).Conclusions Residents are more likely than consultant-grade physicians to seek help when suffering from mental disorders. Local primary prevention actions since the beginning of their training period and having access to a well-known highly reliable programme may partly explain these findings.